FREQUENCY OF INTESTINAL PARASITIC INFESTATION IN CHILDREN OF 5-12 YEARS OF AGE IN ABBOTTABAD - Ahmed, Akbar K.; Malik, Babar; Shaheen, Babar; Yasmeen, Ghazala; Dar, Junaid Babar; Mona, Altaf K.; Gulab, Shamshad; Ayub, Muhammad (Journal of Ayub Medical College Abbottabad, 2003)
Background: Worm infestation is a major problem in children from developing countries due to bad hygienic conditions. It produces nutritional deficiencies and anaemia in children, especially when hookworm infestation is present. Methods: This cross-sectional study deals with investigation of the frequency of intestinal parasitic infestation in children between the ages 5-12 years. A total of 283 subjects were tested and screened for different intestinal parasites at of Department of Physiology, Ayub Medical College, Abbottabad. Negative cases were re-examined and if found free of intestinal pathogenic parasites were labelled as negative. Results: Of the 283 children examined, 230 tested positive for various intestinal parasites. The frequency of helminthic infestation was found to be above 81%. There were 8 different species of helminths and protozoa found in the specimens. By far the highest frequency of 48% was noted for Ascaris lumbricoides while 6.9% (16 cases) of the specimens examined had mixed infestation. The mean Haemoglobin (Hb) level was found to be 9.82 g/dl in males and 9.0 g/dl in females. Virtually no Hookworm infestation was found which may be the reason of not so low Hb level of the subjects. Conclusions: A very high percentage (81%) of children from suburbs of Abbottabad have intestinal worm infestation and majority of them (48% of positive cases) have Ascaris lumbricoides. Children were not very severely anaemic because of virtually no hook worm cases. Key Words: Anaemia, Ascaris lubricoides, Helminths, Intestinal disease parasitic, Child nutritional disorders, Hookworm infestations.